Differences in nature of electrical conductions among Bi4Ti3O12-based ferroelectric polycrystalline ceramics - Changbai Long; Qi Chang; Huiqing Fan (Scientific Reports, 2017)
Abstract Bismuth titanate Bi4Ti3O12 (BiT), was one of the most promising lead-free high-temperature piezoelectric materials, due to high Curie temperature (675 °C) and large spontaneous polarization (50 µC/cm2); however, extensive studies had revealed that high leakage conductivity interferes with the poling process, hindering its practical applications. In this paper, an electrically insulating property was achieved by a low level Nb donor substitution to suppress a high level of holes associated with high oxygen vacancy concentration. Bi4Ti2.97Nb0.03O12 ceramic showed significant enhancements of electrical resistivity by more than three order of magnitude and activity energy with value >1.2 eV, which are significant for piezoelectric applications of BiT-based materials. However, pure and A2O3-excess (A = Bi, La and Nd; 3 at %) BiT ceramics, were mixed hole and oxygen ion conductors. Schottky barriers were both formed at grain boundary region and the sample-electrode interface, because of the existence of semiconducting bulk. Interestingly, the electron conduction could be suppressed in N2, as a consequence, they became oxide ion conductors with conductivity of about 4 × 10−4 S cm−1 at 600 °C.